2021
DOI: 10.3390/cells11010016
|View full text |Cite
|
Sign up to set email alerts
|

The Nerve Growth Factor Metabolic Pathway Dysregulation as Cause of Alzheimer’s Cholinergic Atrophy

Abstract: The cause of the loss of basal forebrain cholinergic neurons (BFCNs) and their terminal synapses in the cerebral cortex and hippocampus in Alzheimer’s disease (AD) has provoked a decades-long controversy. The cholinergic phenotype of this neuronal system, involved in numerous cognitive mechanisms, is tightly dependent on the target-derived nerve growth factor (NGF). Consequently, the loss of BFCNs cholinergic phenotype in AD was initially suspected to be due to an NGF trophic failure. However, in AD there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 161 publications
(219 reference statements)
1
11
0
Order By: Relevance
“…Evidence towards the importance of the nerve growth factor, particularly in neurodegenerative diseases, piled on mainly after the 1970s, resulting in the researchers only receiving the due accolades with the Nobel in 1986. 7,[16][17][18] HER POLITICAL AND SOCIAL WORK Throughout her life, Rita was very politically active. In 2001, she was made senator for life, and although she considered it a very stressful experience, she never lost a session.…”
Section: The Discovery Of Growth Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence towards the importance of the nerve growth factor, particularly in neurodegenerative diseases, piled on mainly after the 1970s, resulting in the researchers only receiving the due accolades with the Nobel in 1986. 7,[16][17][18] HER POLITICAL AND SOCIAL WORK Throughout her life, Rita was very politically active. In 2001, she was made senator for life, and although she considered it a very stressful experience, she never lost a session.…”
Section: The Discovery Of Growth Factorsmentioning
confidence: 99%
“…Her discovery of the nerve growth factor paved the way for our current comprehension of neurodegeneration. [16][17][18]…”
Section: The Discovery Of Growth Factorsmentioning
confidence: 99%
“…Recent data from preclinical studies demonstrate that the consequences of adult or developmental EtOH exposure resemble advanced brain aging or produces accelerated AD-related pathology in transgenic models with AD-related transgenes [80][81][82][83]. Advanced aging, AD, and AUD have some overlapping neuropathological sequelae: upregulation of proinflammatory markers, suppressed hippocampal neurogenesis, suppression of basal forebrain cholinergic phenotype, and altered pro-and mature NT levels-as well as a change in the ratio of Trk to p75 NTRs [84][85][86][87][88]. A common pathway for cholinergic dysfunction in AD and AUD is the disruption of neurotrophins and their receptors (see Figure 2), which may drive additive effects of AD and AUD pathology.…”
Section: Proposed Mechanism Of the Regulation Of Phasic And Tonic Ace...mentioning
confidence: 99%
“…Because of the severe neurodegeneration of the cholinergic neurons in the basal forebrain and linkage with cholinergic input and cognitive function in AD, NGF signaling has been indicated as a key modulator of AD pathology [ 81 ]. Meta-analysis of 98 articles investigating neurotrophic factor levels in CSF and the blood of AD patients showed increased NGF levels in CSF of AD patients [ 82 ].…”
Section: Bdnf and Ngf Signaling In Alzheimer’s Diseasementioning
confidence: 99%
“…A systematic review covering 23 post-mortem studies of AD patients showed that most studies suggested increased proNGF levels in the hippocampus and neocortex of patients with AD [82]. As a mechanism of proNGF accumulation in the AD brain, it has been proposed that there are disturbances in the conversion of proNGF to NGF [81]. Bruno et al (2006) demonstrated that NGF is produced in the synaptic cleft via a coordinated release of proNGF, zymogens, convertases, and endogenous regulators in an activity-dependent manner [83].…”
Section: Bdnf and Ngf Signaling In Alzheimer's Diseasementioning
confidence: 99%